A case work approach with children who stammer - RK, Upadhyay (Journal of All India Institute of Speech and Hearing, 1972)
The child guidance clinics often receive patients with stammering. These patients, generally, come after all the available medical examinations have been tried. This is because in our country, such a problem is supposed to be a medical subject. When such cases are received it becomes easier to look for the causes of stammering. The factors contributing and precipitating lie mostly in the child’s socio-emotional spheres